Synthesis and Antibacterial Activity of Polyalthic Acid Analogs - Marcela Nunes Argentin; Felipe de Paula Nogueira Cruz; Ariana Borges Souza; Elisa Marcela de Oliveira D'Aurea; Jairo Kenupp Bastos; Sérgio Ricardo Ambrósio; Rodrigo Cassio Sola Veneziani; Ilana Lopes Baratella Cunha Camargo; Cassia Suemi Mizuno (MDPI AG, 2023)
Polyalthic acid (PA) is a diterpene found in copaiba oil. As a continuation of our work with PA, we synthesized PA analogs and investigated their antibacterial effects on preformed biofilms of Staphylococcus epidermidis and determined the minimal inhibitory concentration (MIC) of the best analogs against planktonic bacterial cells. There was no difference in activity between the amides 2a and 2b and their corresponding amines 3a and 3b regarding their ability to eradicate biofilm. PA analogs 2a and 3a were able to significantly eradicate the preformed biofilm of S. epidermidis and were active against all the Gram-positive bacteria tested (Enterococcus faecalis, Enterococcus faecium, S. epidermidis, Staphylococcus aureus), with different MIC depending on the microorganism. Therefore, PA analogs 2a and 3a are of interest for further in vitro and in vivo testing to develop formulations for antibiotic drugs against Gram-positive bacteria.